Learning at the Site of Doing; Building Women’s Climate Resilience through Gender-responsive CSA : Insights from AICCRA Ghana - Obeng, Adomaa. F (2025)
Climate-smart agriculture (CSA) innovations, and climate information services (CIS) can help farmers adapt to climate change and improve resilience. However, these innovations must have intentional design elements and implementation strategies that specifically address the unique needs, constraints, and preferences of women farmers to ensure equity and inclusivity. In AICCRA Ghana, gender responsiveness was anchored in intentionality in prioritizing and disseminating CSA and CIS innovations in ways that respond to the lived realities of women and other vulnerable groups. Through the implementation of AICCRA, it has been learnt that Intentionally designing CSA innovations to meet the specific needs of women farmers can build their resilience and ensure equitable adaptation that engenders empowerment outcomes for women. Involvement of women in the design and implementation of climate solutions is key in addressing their challenges.